Kurangnya Minat Baca di Kalangan Mahasiswa : Studi Kasus di Universitas Muhammadiyah Maumere - Yeremias Bardi; Rikarda Nivani Dholo Bala Maria Ermelinda Bunga; Fransiska Putri Andriany; Anastasia Doa Nestiana Pare; Risky Afrizal Donatus Datoq; Wahban Az Zuhaili Razak Misbah Nurrahim (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
The lack of interest in reading among students results in a lack of ideas and opinions in arguing innovatively and creatively which is evident in assignment presentations and producing works. This journal uses a library research method by utilizing articles, journals, books, and internet access as sources. This journal aims to determine the impact of the lack of interest in reading among students, the impact of low interest in reading among students and how to increase interest in reading among teenagers. The results obtained in this study are the impact of low interest in reading among students can affect their lack of ability in mastering the field of science and how to increase interest in reading among students improve library services in schools and the community environment the availability of reading materials allows each person to choose what suits their interests and interests. The conclusion of this study is that the impact of the lack of interest in reading among students can affect the progress of the nation and its human resources.